Poltava Region in World Trade Processes: Realities and Perspectives (Economics and region, 2020)
The current state of foreign economic activity of Poltava region is investigated, the main problems that hinder export-import operations are identified. The factors influencing the activation of international trade operations of the region are summarized and the perspective directions of improvement of foreign economic activity are substantiated.
Keywords: international trade; foreign economic activity; regional economy; Poltava region; investment attractiveness